Bioelectric Membrane Potential and Breast Cancer: Advances in Neuroreceptor Pharmacology for Targeted Therapeutic Strategies - Chitaranjan Mahapatra; Jineetkumar Gawad; Chandrakant Bonde; Mahesh B. Palkar (Receptors, 2025)
Bioelectric membrane potentials regulate cellular growth, differentiation, and movement. Disruptions in bioelectric signaling are strongly linked to cancer development, as abnormal membrane potentials and ion channel activity can drive tumor progression. In breast cancer, ion channel dysfunction and neuroreceptor-related pathways play significant roles in the cell cycle, epithelial–mesenchymal transition, angiogenesis, inflammation, the tumor microenvironment, and tumor progression. Neuroreceptors are critical not only in initiating and advancing cancer but also in conferring resistance to treatments. Neuroreceptors also play a key role, with dopamine receptor D2 activation reducing breast tumor growth by 40% in preclinical models, while serotonin signaling has been shown to promote epithelial–mesenchymal transition (EMT), increasing invasiveness. Advances in understanding these biological mechanisms could lead to more cost-effective and less invasive therapeutic strategies to treat tumors. This review explores the expanding evidence connecting bioelectric activity to breast cancer, focusing on neuroreceptor pharmacology as a transformative therapeutic approach. Examining the modulation of bioelectricity through neuroreceptor pharmacology to influence breast cancer progression and integrating these insights into therapeutic development offers a promising path for addressing treatment challenges and improving precision in managing aggressive cancer subtypes.